Consumption - Hudson, Ian, 1967-; Hudson, Mark, 1971 June 27- (Cambridge, U.K. : Polity Press, 2021)
"A crystal-clear guide to how consumption greases the wheels of modern capitalism"--
The Meanings of Consumption -- An Aspiration for All the World: Championing Individual Freedom of Choice -- The System: Capitalist Consumerism -- Private Choices, Public Problems -- The Shopocalypse -- Consumption, Power, and Liberation -- Shopping Police.
Includes bibliographical references and index.
Keywords: Consumption (Economics); Capitalism